(untitled) (TAJDID: Jurnal Ilmu Ushuluddin, 2024)
This research examines a book Maj’mū’ah al-Shāri’ah al-Kāfiyah li al-’Awwām. One of a phenomenal works of the nationalist figure, Kiai Sholeh Darat Semarang. The book is written in pegon script in Javanese. This is a special strategy used by Kiai Sholeh Darat in spreading the message of Islam under the pressure and authoritarianism of the Dutch. Although this book is basically a fiqh book, Kiai Sholeh Darat added certain chapters to discuss general issues, one of which is the problems faced by the Indonesian people. Kiai Sholeh Darat highlighted the habits of the Indonesian people regarding taṭayyur, he then expressed his ideas and quoted several matan hadith. This study aims to examine Kiai Sholeh Darat’s thoughts on the traditions of taṭayyur in the book Maj’mū’ah al-Shāri’ah al-Kāfiyah li al-’Awām. This type of research is library research and the method used is qualitative. The theory used in this study is the theory of understanding hadith by Muḥammad al-Ghazālī. The result of the research is a prohibition on the whole concept of taṭayyur. Either going to a fortune teller to find out his fate or believing in the existence of bad luck that comes not from God but from certain things such as unlucky days.